Associations Between Physical Activity, Social Wellbeing, and Study Engagement Among Finnish Students (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The aim of this study was to investigate the cross-sectional associations between physical activity, social wellbeing, and study engagement among Finnish early adolescents. Despite growing interest in these topics, previous research has largely overlooked their interconnectedness. This study aims to fill that gap by providing new insights into how these variables associate with one another.Methods: A total of 813 Finnish adolescents participated in the study (426 girls, 346 boys, and 41 with missing gender information). The sample included 362 grade five students and 451 grade eight students. Students’ physical activity, social wellbeing, and study engagement were measured using a questionnaire comprising the following validated instruments: physical activity was measured using a self-reported questionnaire, social wellbeing was measured with the Classroom Peer Context Questionnaire, and study engagement was measured using the Schoolwork Engagement Inventory. Data were analysed using descriptive statistics and Pearson’s correlation coefficients.Results: Study engagement was assessed through three dimensions: energy, dedication, and absorption. A statistically significant small correlation was found between physical activity and energy (.127, p < .001) whereas no association was found between physical activity and dedication (.078, p .031) or absorption (.052, p .146). From the five subdimensions of social wellbeing, physical activity was associated with comfort (.145, (p < .001), cooperation (.125, p < .001), and cohesion (.109, p .002), but not with conflict (–.051, p < .157) and isolation (–.047, p < .194).Conclusion: The findings of this study suggest that adolescents’ physical activity is positively linked to study engagement and social wellbeing. In other words, students with higher physical activity also have higher study engagement and social wellbeing, and vice versa. The associations were significant but weak, indicating the need for further research using more diverse and comprehensive analytical methods to better understand the broader role of physical activity in supporting adolescents’ overall school experience.Support/Funding Source: This research was funded by the Strategic Research Council of Finland [Grant Number 1352509]. Study is part of the SchoolWell consortium which is a large multidisciplinary consortium that studies children’s comprehensive wellbeing at school in Finland.